An Assessment of Comparative Advantage of Mauritius - Mushanyuri, Bongani Edwin; Mzumara, Macleans (European Journal of Sustainable Development, 2013)
The authors investigated whether Mauritius has comparative advantage in theproducts it exports in intra-SADC, intra-COMESA and global markets. There is aneed for Mauritius to improve its competitiveness through a combination of bothregional and national strategies via increasing investment in infrastructuraldevelopment, promotion of intra-regional trade and integration, improvingcapacity building, liberalization of the labour market and facilitating the access tobanking resources. The results showed that Mauritius has a revealed comparativeadvantage (RCA) index of ?1 in 529 product codes. The highest RCA index of1694.21 was found in live primates.